Dlug - Krauze, Krzysztof (Poland : Studio Filmowe Zebra, 1999)
A gripping thriller about two entrepreneurs who become tangled in the web of a Russian thug. Two friends begin a business venture of importing Italian scooters into Poland. With no collateral, they turn to a Russian acquaintance that offers money and support in the beginning and then inexplicably turns violent and vicious. Tension mounts as the two friends begin to understand what must be done. Based on a true story, "The Debt" is a terrifying tale of ordinary men pushed to their limit. Stars Robert Gonera, Jacek Borcuch, Andrzej Chyra.
Duration: 01:37:00
Keywords: Fiction films